Trend Analysis of Positive Sentiment for Special Autonomy for Papua on Twitter - Lawelai, Herman; Sadat, Anwar (Research and Development Agency Ministry of Home Affairs, 2022)
Technological Advances encourage internet users on mobile phones or other communication tools to access or obtain information via social media, including conversations on social media on Twitter, about the implementation of Provincial special autonomy. This research method utilizes Twitter data crawled by the Drone Emprit Academic application with the keyword